2022
DOI: 10.47814/ijssrr.v5i4.225
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual Capital and Financial Performance in Sharia Commercial Banks in Indonesia

Abstract: This study measures the value-added intellectual coefficient (VAICTM) for the efficient performance of Islamic banking in Indonesia. In addition, this study examines the relationship between the efficiency of Intellectual Capital and Financial Performance. This paper uses secondary data collected from quarterly reports for 2015-2020 on BUMN Islamic Banks; BNI Syariah, BRI Syariah, and Bank Mandiri Syariah. Data analysis using SEM (Structural Equation Modeling) using Partial Least Square (PLS) analysis. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…Financial performance in this mini-research uses Return on Equity (ROE). ROE measures the rate of return on shares owned by company shareholders (Aisyah & Pratikto, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Financial performance in this mini-research uses Return on Equity (ROE). ROE measures the rate of return on shares owned by company shareholders (Aisyah & Pratikto, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Another study conducted by Astari (2015), in a manufacturing company in Indonesia concluded that intellectual capital, particularly human capital (HC), has a significant impact on financial performance, proxied by Return On Equity (ROE) and the firm's value measured by Price to Book Value (PBV). In line with this, a study by Rizkyanti et al (2020), conducted on 14 Islamic banks in Indonesia demonstrated that intellectual capital (VACA, VAHU, STVA) significantly influences the performance of Islamic banks. Furthermore, another study concluded that knowledge management and intellectual capital, when considered together, significantly impact firm performance (Rehman et al, 2022).…”
Section: Introductionmentioning
confidence: 62%
“…Value Added Human Capital (VAHU) memberikan pengaruh yang negatif dan signifikan terhadap Return on Assets (ROA) berdasarkan hasil estimasi dengan koefisien -0.0271 dan probabilitas 0.00. Hasil ini sejalan dengan penelitian yang dilakukan oleh Aisyah et al (2022); Dodik Suprayogi et al (2020); Harahap et al (2020); dan Harianja et al (2020) yang menyatakan bahwa Value Added Human Capital (VAHU) memberikan pengaruh yang signifikan terhadap Return on Assets (ROA). Hal ini bisa disebabkan oleh beberapa hal seperti inefisiensi penggunaan sumber daya manusia.…”
Section: Pengaruh Structural Capital Value Added (Stva) Terhadap Retu...unclassified